Analisis Yuridis Kekerasan Gender Berbasis Online (KGBO) dengan Deepfakes Ditinjau dari Hukum Positif - Criswara, Nadila (Proceedings Series on Social Sciences & Humanities, 2024)
The rapid progress of technology in this digital era has both positive and negative impacts, Technological progress is accompanied by societal development, so many new problems will emerge in people's lives. These new problems arose without being accompanied by progressive law, so in this case, the law staggered with developments over time. One example of technological progress is artificial intelligence (AI) technology. One example is the misuse of deepfakes in online gender violence (KGBO), namely by falsifying photos or videos by inserting facial photos into other photos or videos so that it is very difficult to see their authenticity. In Indonesia, there are no laws and regulations that explicitly regulate this matter, so other related laws and regulations are usually used. This article discusses the regulations regarding online gender violence with deepfakes through existing regulations in Indonesia. In its discussion, this article uses the ius constitutum in Indonesia and compares various types of relevant laws and regulations. The discourse discussed is: How is the misuse of deepfake a criminal act, and what is the criminal responsibility for it in Indonesia? Then this article focuses on normative juridical methods by reviewing them comprehensively through statutory regulations.